Pengaruh Corporate Social Responsibility, Kepemilikan Manajerial, Dan Capital Intensity Terhadap Tax Avoidance - Agustyo, Bagas Arya; Arianti, Baiq Fitri (Gorontalo Accounting Journal, 2024)
This study aims to obtain empirical evidence of the effect of corporate social responsibility, managerial ownership and capital intensity on tax avoidance. This type of research uses a quantitative approach. The data used is secondary data in the form of financial statements. The population in this study are manufacturing companies, especially the primary consumer goods industry sector listed on the Indonesia Stock Exchange in 2017-2021. The samples used in this study amounted to 12 manufacturing companies with a 5-year observation period in the 2017-2021 period and the number of financial reports sampled in this study amounted to 60. The results of the research conducted show that corporate social responsibility, managerial ownership, and capital intensity have an effect on tax avoidance, corporate social responsibility has no effect on tax avoidance, managerial ownership has a negative effect on tax avoidance and capital intensity has no effect on tax avoidance.